EFEKTIVITAS PROSES PEMBELAJARAN PENDIDIKAN PANCASILA DITINJAU DARI MANAJEMEN WAKTU DAN CAPAIAN DIMENSI PROFIL LULUSAN PADA FASE C DI SEKOLAH DASAR - Salma Danish Ara Prasodjo; Aulia Rahma Talitha; Putri Mulyanti; Cheessavana Bella Aullia; Windi Winandari; Hamid; Nur Indah Wahyuni (STKIP Subang, 2025)
This study aims to analyze the effectiveness of the Pancasila Education learning process in Phase C of elementary school by examining time management practices and the achievement of the Profile of Pancasila Students dimensions. The research is motivated by the mismatch between planned instructional time and actual classroom implementation under the Independent Curriculum, which affects learning dynamics and student competency development. This study employed a qualitative descriptive method with a case study approach at SDN Tugurejo 03 Semarang. Data were collected through classroom observations, in-depth interviews with teachers, and documentation of lesson plans and learning records. The results show that the initial stage of learning was well-managed; however, time constraints began to arise during the main activities and became more apparent at the closing stage. Limited time, transitions before break time, and fluctuating student focus prevented deeper reflection and reinforcement. These conditions influenced the achievement of the Pancasila Student Profile dimensions, especially in communication, independence, and critical thinking, which had not yet developed optimally—particularly for students with low basic literacy skills. Meanwhile, collaboration, creativity, and moral values emerged more consistently through contextual and cooperative activities. The findings highlight that the effectiveness of Pancasila Education is strongly influenced by adaptive time management and classroom readiness. The study recommends flexible time allocation strategies, improved scheduling to support student concentration, and differentiated support for students with special needs, serving as practical input for improving the implementation of the Independent Curriculum.